2020
DOI: 10.3390/catal10121415
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Reactions of Air-Quality Protection on Eco-Friendly Iron-Based Catalysts

Abstract: A series of iron functionalized hydroxyapatite (Fe/HAP) samples with different metal loading (2 < wt.% Fe < 13) was prepared by a flash ionic exchange procedure from iron(III) nitrate as precursor and tested in some environmental air-quality protection reactions such as the catalytic reduction of NOx by NH3 (NH3-SCR), catalytic oxidation of NH3 (NH3-SCO) and catalytic N2O decomposition. The catalytic performances of the Fe/HAP catalysts were determined under flow conditions as a function of temperature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 45 publications
(59 reference statements)
2
16
0
Order By: Relevance
“…In this drastic scenario, over the years numerous strategies have been developed and properly optimized with the final aim of decomposing NOx species. Among all the possibilities, their selective catalytic reduction by ammonia as a reducing agent (NH 3 -SCR) is one of the most studied and applied technologies [ 7 , 8 , 9 ], as well as absorption and adsorption routes [ 6 , 10 ]. However, from a practical viewpoint all these techniques suffer from several drawbacks, limiting their real application [ 3 , 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this drastic scenario, over the years numerous strategies have been developed and properly optimized with the final aim of decomposing NOx species. Among all the possibilities, their selective catalytic reduction by ammonia as a reducing agent (NH 3 -SCR) is one of the most studied and applied technologies [ 7 , 8 , 9 ], as well as absorption and adsorption routes [ 6 , 10 ]. However, from a practical viewpoint all these techniques suffer from several drawbacks, limiting their real application [ 3 , 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the core size and loading of Fe were controlled by adjusting synthesis parameters, while the packaging process of the multilayer material was irrelevant to the properties of iron oxide in the nucleus . Meanwhile, the magnetic core-shell structure materials as a magnetic separable carrier can be utilized in the field of water purification and the like by composite or modification with other materials. , …”
Section: Introductionmentioning
confidence: 99%
“…25 Meanwhile, the magnetic core-shell structure materials as a magnetic separable carrier can be utilized in the field of water purification and the like by composite or modification with other materials. 26,27 Fe 2 O 3 has the most stable phase among all iron oxides, in which γ-Fe 2 O 3 is a magnetic substance with a cubic or tetragonal structure. It has become the subject and interest of modern material research due to its unique and fascinating magnetic, electrical, and dielectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…[20], thereby making exchanged HAp efficient catalytic systems. Accordingly, the synthesis and study of HAp-based catalytic systems with iron impurities have attracted great interest in recent years [21][22][23][24][25][26]. As reviewed by Goldberg et al [27,28], Fe-HAp and Fe oxide nanoparticles demonstrated high efficiency as a catalyst in the field of heavy oil purification via oxidative desulfurization and aquathermolysis methods, oil asphaltene extraction, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[20], thereby making exchanged HAp efficient catalytic systems. Accordingly, the synthesis and study of HAp-based catalytic systems with iron impurities have attracted great interest in recent years [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%